To complete the square for the quadratic equation \( y = x^2 - 16x + 14 \), we follow the steps:
-
Take the coefficient of \( x \) (which is -16), divide it by 2 to get -8, and then square it to get 64.
-
Rewrite the equation, adding and subtracting this square:
\[ y = (x^2 - 16x + 64) - 64 + 14 \]
-
Simplify the equation:
\[ y = (x - 8)^2 - 64 + 14 \] \[ y = (x - 8)^2 - 50 \]
-
This shows that the vertex form of the equation is \( y = (x - 8)^2 - 50 \).
The vertex of the parabola is at the point \( (8, -50) \).
Therefore, the answer is:
(8, -50)